2013
DOI: 10.1007/s00424-013-1391-0
|View full text |Cite
|
Sign up to set email alerts
|

Preserved cross-bridge kinetics in human hypertrophic cardiomyopathy patients with MYBPC3 mutations

Abstract: Mutations in the MYBPC3 gene, encoding cardiac myosin binding protein C (cMyBP-C) are frequent causes of hypertrophic cardiomyopathy (HCM). Previously, we have presented evidence for reduced cMyBP-C expression (haploinsufficiency), in patients with a truncation mutation in MYBPC3. In mice, lacking cMyBP-C cross-bridge kinetics was accelerated. In this study, we investigated whether cross-bridge kinetics was altered in myectomy samples from HCM patients harboring heterozygous MYBPC3 mutations (MYBPC3mut). Isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…This result was also observed following shRNA-mediated MYBPC3 knockdown in otherwise normal cells. Our results are supported by measurements in adult patient-derived cells assessed in vitro where a 30%–40% decrease in maximum Ca 2+ -activated force development has been observed in cells with the c.2373insG mutation, and a mechanism of haploinsufficiency suggested ( van Dijk et al., 2009 , van Dijk et al., 2014 , Witjas-Paalberends et al., 2013 ). Importantly, the force generation defects we observed here were in non-hypertrophic cells, suggesting a primary event not consequential to hypertrophy and related maladaptive processes.…”
Section: Discussionsupporting
confidence: 83%
“…This result was also observed following shRNA-mediated MYBPC3 knockdown in otherwise normal cells. Our results are supported by measurements in adult patient-derived cells assessed in vitro where a 30%–40% decrease in maximum Ca 2+ -activated force development has been observed in cells with the c.2373insG mutation, and a mechanism of haploinsufficiency suggested ( van Dijk et al., 2009 , van Dijk et al., 2014 , Witjas-Paalberends et al., 2013 ). Importantly, the force generation defects we observed here were in non-hypertrophic cells, suggesting a primary event not consequential to hypertrophy and related maladaptive processes.…”
Section: Discussionsupporting
confidence: 83%
“…HCM-associated MYBPC3 mutations, especially those that reduce the amount of cMyBP-C, promote a loss of cross-bridge cycling inhibition. The loss of cMyBP-C regulation has been shown to decrease maximal force development in samples of human tissue from mutation carriers (van Dijk et al, 2014) and in mouse models of disease (Barefield et al, 2014a; Harris et al, 2002). However, these MYBPC3 mutations have been shown to increase the energetic cost of contraction similar to MYH7 mutations (Witjas-Paalberends et al, 2014b).…”
Section: Hypertrophic Cardiomyopathy and Thick Filament Gene Mutationsmentioning
confidence: 99%
“…They showed that, although maximal force development was reduced, the rates of force redevelopment, stretch activation and cross-bridge kinetics did not differ significantly. This suggested that cross-bridge kinetics were not altered, a finding that was consistent with haploinsufficiency (van Dijk et al 2013). In another paper, Kuster et al (2013) hypothesized that microRNAs played a role in HCM.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 75%